The clinical risk and post-COVID-19 sequelae in patients with myasthenia gravis: a retrospective observational study - Chaoyue Zhang; Haocheng Luo; Yufei Deng; Hongjin Li; Xiang Yu; Jiaxin Liu; Linqi Huang; Xiaojun Yang; Qilong Jiang (Frontiers in Neurology)
BackgroundThere are indeed several studies addressing the severity of Coronavirus disease 2019 (COVID-19) infection in myasthenia gravis (MG) patients. However, data on post-COVID-19 sequelae in MG patients remain limited. To address this gap, we collected clinical data on the condition and prognosis of MG patients with COVID-19 infection, aiming to investigate factors influencing both the severity of the infection and the occurrence of post-COVID-19 sequelae at 1 and 12 months after recovery.MethodThis was a retrospective analysis of 150 MG patients with COVID-19 infection from November 1, 2022 to March 1, 2023 at the First Affiliated Hospital of Guangzhou University of Chinese Medicine, including patient demographics, clinical characteristics, and post-COVID-19 sequelae. Multivariable binary logistic and linear regression models were employed to ascertain the variables influencing the severity. The evolution of the post-COVID-19 sequelae was analyzed using McNemar's test.ResultIn 150 MG patients, 128 (85.3%) patients were presented with COVID-19 infection, and 23 (18%) patients were hospitalized. The severity was associated with the daily corticosteroid dose (OR = 1.08, p = 0.02) and the frequency of myasthenia crises pre-COVID-19 (b = 7.8, t = 2.14, p = 0.035). Compared to normal patients, MG patients are more likely to experience post-COVID-19 sequelae such as insomnia, myalgia, dizziness, cough, expectoration, and sore throat at 12 months after recovery. Among these, the prevalence of myalgia, dizziness, rash, and vision impairment was significantly higher.ConclusionCompared to normal patients, MG patients are prone to developing severe COVID-19 infection, which is associated with the daily corticosteroid dose and the frequency of myasthenia crises pre-COVID-19. Additionally, they are prone to experiencing post-COVID-19 sequelae, including insomnia, myalgia, dizziness, cough, expectoration, and sore throat, at 12 months after recovery.